Pola Asuh Orang Tua dalam Membentuk Kepribadian Islami Pada Anak Usia Dini di Raudhatul Athfal (RA) Hidayatus Sibyan Kandanghaur - Zakiyatul Muhandisah (LPPM STAIS Dharma Indramayu, 2021)
Family is the most important element in shaping the personality of early childhood. The right parenting pattern will be able to form a good early childhood personality. This study was structured to determine parenting patterns in shaping the character of early childhood. The research location for this thesis is RA Hidayatus Sibyan Kandanghaur. This study uses a descriptive qualitative research method that combines data sources from the field and data sources from references related to the theme of this thesis. The results of this study are: (1) that the type of parenting that is mostly done by parents at RA Hidayatus Sibyan is democratic parenting, although in certain cases authoritarian parenting is also used by parents with the aim of assertiveness. The parenting style of neglect and indulgence is usually carried out by guardians of students who are not biological parents (father / mother), such as relatives or grandparents. (2) The education factor of parents who are mostly under high school who become guardians of students at RA Hidayatus Sibyan lacks adequate insight into the psychology of early childhood development. (3) The relationship between parents and teachers at RA Hidayatu Sibyan is quite good, such as having relationships not only at school but also in community interactions.